Will Virtual Reality Experience Quality be an Alternative to Offline Visit Decision? Review of Literature on Tourist Behaviour on Instagram Social Media - Kusumawati, Andriani; Pangestuti, Edriana; Rahayu, Karisma Sri (Media Konservasi, 2024)
Virtual reality is the latest addition to the tourism industry, leveraging advancements in Internet technology. The advent of Virtual Reality (VR) tourism technology offers a comprehensive portrayal of tourist destination details and mitigates customer apprehension or uncertainty by acquainting consumers with unfamiliar locales. Virtual reality is a highly captivating advancement in tourism marketing that enables consumers to immerse themselves in and encounter destinations in real-time. The objective of this study is that explains how virtual reality can be used to replace traditional offline decision-making processes in the tourism industry. This study employs a comprehensive review of existing literature on the utilisation of virtual reality and its influence on offline visitation choices. Subsequently, a conceptual framework and research hypotheses are formulated. This research paper explores the behaviour of tourists who engage in offline or virtual experiences. Multiple articles were assessed for future research advancements. The findings of this study reveal distinct patterns of tourist behaviour, particularly among millennials, in relation to their ability to adapt to technological advancements. The research findings are anticipated to offer both theoretical and practical benefits to stakeholders involved in tourism technology, particularly in its application as a marketing instrument.